A novel animal model of acquired human temporal lobe epilepsy based on the simultaneous administration of kainic acid and lorazepam. (February 2017) - Kienzler‐Norwood, Friederike; Costard, Lara; Sadangi, Chinmaya; Müller, Philipp; Neubert, Valentin; Bauer, Sebastian; Rosenow, Felix; Norwood, Braxton A.
Summary: Objective: Kainic acid (KA) is a potent glutamate analog that is used to induce neurodegeneration and model temporal lobe epilepsy (TLE) in rodents. KA reliably induces severe, prolonged seizures, that is, convulsive status epilepticus (cSE), which is typically fatal without pharmacologic intervention. Although the use of KA to model human epilepsy has proven unquestionably valuable for >30 years, significant variability and mortality continue to confound results. These issues are probably the consequence of cSE, an all‐or‐nothing response that is inherently capricious and uncontrollable. The relevance of cSE to the human condition is dubious, however, as most patients with epilepsy never experienced it. We sought to develop a simple, KA‐based animal model of TLE that avoids cSE and its confounds. Methods: Adult, male Sprague‐Dawley rats received coincident subcutaneous injections of KA (5 mg) and lorazepam (0.25 mg), approximately 15.0 and 0.75 mg/kg, respectively. Continuous video–electroencephalography (EEG) was used to monitor acute seizure activity and detect spontaneous seizures. Immunocytochemistry, Fluoro‐Jade B staining, and Timm staining were used to characterize both acute and chronic neuropathology. Results: Acutely, focal hippocampal seizures were induced, which began after about 30 min and were self‐terminating after a few hours. Widespread hippocampal neurodegeneration was detected after 4 days. Spontaneous, focal hippocampal seizures began after an average of 12 days in all animals. Classic hippocampal sclerosis and mossy fiber sprouting characterized the long‐term neuropathology. Morbidity and mortality rates were both 0%. Significance: We show here that the effects of systemic KA can be limited to the hippocampus simply with coadministration of a benzodiazepine at a low dose. This means that lorazepam can block convulsive seizures without truly stopping seizure activity. This novel, cSE‐free animal model reliably mimics the defining characteristics of acquired mesial TLE: hippocampal sclerosis and spontaneous hippocampal‐onset seizures after a prolonged seizure‐free period, without significant morbidity, mortality, or nonresponders.